Application of comprehensive scene simulation teaching based on 2PM teaching mode in the practice course of Internal Medicine Nursing (基于2PM教学模式的综合性情景模拟教学在《内科护理学》实践课程中的应用) - WANG Jinxia (王金霞); JIANG Yuanfang (姜元方); FAN Linlin (范琳琳) (中西医结合护理)
Objective To explore the application effect of comprehensive scene simulation teaching based on 2PM teaching mode in the practice course of Internal Medicine Nursing. Methods A non-randomized controlled trail was conducted, and 125 nursing undergraduates of grade 2017 were divided into observation group(n=62) and control group(n=63). The observation group adopted the comprehensive scene simulation teaching method based on 2PM teaching mode, while the control group adopted the traditional teaching method. A questionnaire was sent out to investigate students' independent learning ability, critical thinking ability and teaching satisfaction. Results After the comprehensive scene simulation teaching based on 2PM teaching mode, the total score and each score of independent learning ability in the observation group were higher than those of the control group (P<0. 05). The total score of critical thinking scale and the scores of open thinking, analytical ability and thirst for knowledge in the observation group were higher than those in the control group (P<0. 05). More than 85. 00% of the students in the observation group were satisfied with the training course. Conclusion The comprehensive scene simulation teaching based on 2PM teaching mode can effectively improve students' critical thinking ability, autonomous learning ability and teaching satisfaction. (目的 探讨基于2PM教学模式的综合性情景模拟教学在《内科护理学》实践课程中的应用效果。方法 采用非随机同期对照试验, 选取学校2017级护理学本科2个班共125名学生, 分别设为观察组(n=62)和对照组(n=63)。观察组学生采用基于2PM教学模式的综合性情景模拟教学法, 对照组学生采用传统教学法。发放问卷调查学生的自主学习能力、批判性思维能力和教学满意度。结果 观察组学生的自主学习量表总分及各项评分均高于对照组(P＜0. 05)。观察组学生的批判性思维量表总分及开放思维、分析能力、求知欲等3个维度评分均高于对照组(P＜0. 05)。观察组学生对本次实训课程满意度超过85%。结论 在《内科护理学》实践课程中采用基于2PM教学模式的综合性情景模拟教学, 能有效提高学生的批判性思维能力、自主学习能力及教学满意度。)